2017
DOI: 10.1007/s00464-017-5805-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications after colonic procedures in chronic obstructive pulmonary disease: does laparoscopy offer a benefit?

Abstract: Despite the potential risks of laparoscopic pneumoperitoneum in the susceptible COPD population, a minimally invasive approach was associated with lower risk of postoperative respiratory complications, shorter length of stay, and decrease in postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Other studies have demonstrated the decrease in pulmonary complications by using minimally invasive techniques. 13 The study by Juo et al showed similar results with the addition of separating out LC and RAC from OC. 12 Furthermore, while the RAC had higher costs, it had the lowest postoperative complications.…”
Section: Discussionmentioning
confidence: 74%
“…Other studies have demonstrated the decrease in pulmonary complications by using minimally invasive techniques. 13 The study by Juo et al showed similar results with the addition of separating out LC and RAC from OC. 12 Furthermore, while the RAC had higher costs, it had the lowest postoperative complications.…”
Section: Discussionmentioning
confidence: 74%
“…Laparoscopic procedures are now widely used within colorectal surgery and many would argue that it is now the standard approach that should be offered to patients (3). Laparoscopic surgery is known to reduce respiratory complications (3); even in COPD patients, despite the perceived increased risks of pneumoperitoneum (4). Reduction in post-operative pain has also been confirmed (5); as has reduced length of stay in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, COPD as a diminished pulmonary status was usually considered as a relative contraindication to laparoscopic major abdominal surgery. Recently, several studies reported that laparoscopic major abdominal surgery was well tolerated by patients with COPD, and no difference was found in postoperative pulmonary complications between the laparoscopic and open procedures [ 10 , 11 ]. Thus, we performed this meta-analysis to assess the safety and feasibility of laparoscopic major abdominal surgery for patients with COPD.…”
Section: Introductionmentioning
confidence: 99%